Portal vein embolization versus radiation lobectomy as pre-treatment for major liver resection for colorectal liver metastases: functional assessment of the future liver remnant - Khalil Ramdhani; Rosalie C. M. van Rees; Daan Andel; Jeanine M. L. Roodhart; Arthur J. A. T. Braat; Rutger C. G. Bruijnen; Inne H. M. Borel Rinkes; Onno Kranenburg; Marnix G. E. H. Lam; Maarten L. J. Smits; Jeroen Hagendoorn (Angiogenesis, 2026)
Introduction Insufficiency of the future liver remnant (FLR) precludes surgery for liver tumors as it is associated with post-hepatectomy liver failure (PHLF). A common strategy to induce pre-operative FLR hypertrophy is portal vein embolization of the tumor bearing liver lobe. More recently, transarterial radio-embolization (radiation lobectomy, RL) has been employed. Direct functional assessment using 99mTc-mebrofenin-hepatobiliary-scintigraphy (HBS) predicts FLR sufficiency more accurately than conventional volume assessment. However, studies describing dynamic functional assessment of the FLR after RL as induction for surgery are currently lacking. This study aims to compare FLR functional changes after PVE and RL. Methods This non-interventional retrospective single-center cohort study was performed between 2016 and 2024. Patients with colorectal liver metastases (CRLM) who underwent PVE or RL because of an insufficient FLR (HBS 2 ) were included. Induction of sufficient FLR function was the primary outcome. Results Ten PVE- and ten RL-treated patients were included. The median duration to achieve sufficient FLR function was longer for RL- than PVE-treated patients (75 days (64–85) vs 31 days (28–54.5), p = 0.002). RL showed a non-significant higher median functional increase (58.6% vs 51.1%, p = 0.940) and a significantly higher voluminal increase (65.7% vs 36.8%, p = 0.049) compared to PVE. PHLF and resection margins were comparable among groups. There was no 90 day mortality. Conclusion RL represents a feasible alternative to PVE with comparable functional outcomes, particularly in patients with lower baseline FLR function or need for simultaneous tumor control. This warrants prospective studies with optimized RL protocols to better define the functional outcomes and clinical applications of RL versus PVE.

Anticipatory governance for responsible investment in energy transition minerals in the Western Congo Basin - F.A Mboringong; R.A. Riggs; J.D. Langston; A.K. Boedhihartono; D. Endamana; Y. Ge; J.L Innes; J. Lu; P. Meyfroidt; L. Weng; J. Sayer (The Extractive Industries and Society, 2025)

Identification of the type locality of the South Island Brown Kiwi Apteryx australis - R. P. Scofield; J. R. Wood; L. de Nascimento; H. A. Robertson; R. M. Colbourne; V. L. De Pietri; J. Innes; J. T. Weir (Conservation Genetics, 2021)

DArTseq molecular markers for resistance to Phytophthora cinnamomi in pineapple (Ananas comosus L.) - G. Sanewski; L. Ko; D. Innes; A. Kilian; J. Carling; J. Song (Australasian Plant Pathology, 2017)

Lateglacial and Holocene relative sea‐level changes and first evidence for the Storegga tsunami in Sutherland, Scotland - Antony J. Long; Natasha L. M. Barlow; Sue Dawson; Jon Hill; James B. Innes; Catherine Kelham; Fraser D. Milne; Alastair Dawson (Journal of Quaternary Science, 2016)
We reconstruct one of the longest relative sea‐level (RSL) records in north‐west Europe from the north coast of mainland Scotland, using data collected from three sites in Loch Eriboll (Sutherland) that we combine with other studies from the region. Following deglaciation, RSL fell from a Lateglacial highstand of +6−8 m OD (Ordnance Datum = ca. mean sea level) at ca. 15 k cal a BP to below present, then rose to an early Holocene highstand and remained at ca. +1 m OD between ca. 7 and 3 k cal a BP, before falling to present. We find no evidence for significant differential Holocene glacio‐isostatic adjustment between sites on the north‐west (Lochinver, Loch Laxford), north (Loch Eriboll) and north‐east (Wick) coast of mainland Scotland. This suggests that the region was rapidly deglaciated and there was little difference in ice loads across the region. From one site at the head of Loch Eriboll we report the most westerly sedimentary evidence for the early Holocene Storegga tsunami on the Scottish mainland. The presence of the Storegga tsunami in Loch Eriboll is predicted by a tsunami wave model, which suggests that the tsunami impacted the entire north coast of Scotland and probably also the Atlantic coastline of north‐west Scotland.

Comparison between open-site and below-canopy climatic conditions in Switzerland for different types of forests over 10 years (1998−2007) - V. Renaud; J. L. Innes; M. Dobbertin; M. Rebetez (Theoretical and Applied Climatology, 2011)

Collisional accretion of a Late Ordovician oceanic island arc, northern Tasman Orogenic Zone, Australia - R. A. Henderson; B. M. Innes; C. L. Fergusson; A. J. Crawford; I. W. Withnall (Australian Journal of Earth Sciences, 2011)

Climate change adaptation and regional forest planning in southern Yukon, Canada - A. E. Ogden; J. L. Innes (Mitigation and Adaptation Strategies for Global Change, 2008)

Climate change adaptation and regional forest planning in southern Yukon, Canada - A. E. Ogden; J. L. Innes (Mitigation and Adaptation Strategies for Global Change, 2008)

Recognition of debris flow, debris flood and flood hazard through watershed morphometrics - D. J. Wilford; M. E. Sakals; J. L. Innes; R. C. Sidle; W. A. Bergerud (Landslides, 2004)

Observation and Confirmation of Foliar Ozone Symptoms of Native Plant Species of Switzerland and Southern Spain - J. M. Skelly; J. L. Innes; J. E. Savage; K. R. Snyder; D. Vanderheyden; J. Zhang; M. J. Sanz (Water, Air, & Soil Pollution, 1999)

Strain-specific deletions in exon 10 of rat K-kininogen and T1-kininogen genes allow mapping of both genes to rat Chromosome 11 Kngk gene AF003624 for the 421 bp fragment of the DRY Kngl1 gene. Locus names and mapping information have been submitted to the Rat Genetic Nomenclature Committee and RATMAP respectively.--> - Eugenie L. Harris; Murray R. Grigor; Brendan A. Innes; Stephen B. Harrap; George Koike; Howard J. Jacob (Mammalian Genome, 1997)